Effects of platelet-rich plasma on human gingival fibroblast proliferation and migration in vitro (Journal of Applied Oral Science, 2022)
Objective: This study evaluated the influence of platelet-rich plasma (PRP) on the behaviour of human gingival fibroblasts (hGFs), including fibroblast proliferation, migration and colony formation. Methods: PRP was obtained from the human peripheral blood of a healthy volunteer and then was diluted into platelet concentrations of 1%, 2% and 5%. The proliferation of hGFs was determined by two methods: (1) Cell-number counting with a haemocytometer method at days 1, 3, 5 and 7; (2) Colony-forming unit-fibroblast (CFU-F) assay at 2 weeks. The migration of hGFs was evaluated with scratch assay, then recorded digital images were analysed by Image-Analysis J 1.51j8 software to compare the remaining artificial wound areas between PRP groups at 0, 24 and 48 hours. Results: All hGFs that were cultivated in media with 1%, 2% and 5% PRP showed their ability to proliferate and migrate. Cell numbers incubated with 1% PRP increased significantly during the first three days and peaked at day 5, tending to be similar to their proliferation in complete medium. With concentrations of 2% and 5% PRP, hGFs outgrew and peaked at day 3, which was faster than with those in medium with 1% PRP. Especially, hGFs in the group 5% PRP proliferated with higher cell numbers than those in the other remaining groups at day 3. The hGF colony number that was formed in the group 5% PRP was significantly higher than those in the groups 1% and 2% PRP. Scratch assay showed hGFs in the groups 2% and 5% PRP almost filled the artificial wound and migrated more effectively than in the group 1% PRP at 24 hours, which was significant. Conclusion:In this study, perhaps the medium with 5% PRP is the dominant option, promoting the abilities of hGFs to heal wounds, because of its fast and effective impact on cell proliferation, colony formation and migration.